2007
DOI: 10.1021/ja0703271
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ammonia Detection by Chemically Functionalized Single-Walled Carbon Nanotubes: InSituElectrical and Optical Study of Gas Analyte Detection

Abstract: We provide definitive evidence for the mechanism of electronic detection of ammonia by monitoring in situ changes in the electrical resistance and optical spectra of films of poly(m-aminobenzenesulfonic acid)-functionalized SWNTs (SWNT-PABS). The increase of resistance during exposure to ammonia is associated with deprotonation of the PABS side chain that in turn induces electron transfer between the oligomer and the valence band of the semiconducting SWNTs. Near IR spectroscopy is used to demonstrate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 34 publications
2
91
0
2
Order By: Relevance
“…The molecular structure and the interaction mechanism of PABS-SWNT with NH , proposed by Bekyarova et al [22], is shown in Fig. 1.…”
Section: Functionalized Cntsmentioning
confidence: 98%
See 1 more Smart Citation
“…The molecular structure and the interaction mechanism of PABS-SWNT with NH , proposed by Bekyarova et al [22], is shown in Fig. 1.…”
Section: Functionalized Cntsmentioning
confidence: 98%
“…The well-defined composition and properties of covalently functionalized SWNTs provide an opportunity to dynamically characterize the nanotube electronic structure and electrical conductivity in the presence of analyte molecules [22].…”
Section: Functionalized Cntsmentioning
confidence: 99%
“…The polymer attracts NH3 and creates a NH4 bonding, where the ammonia gas particle is physically attached to the SWNT. This is also hydrophilic, which allows it stay well suspended in water solution for inkjet printing purposes [13].…”
Section: ) Inkjet Printing Of Carbon Nanotubes (Cnts)mentioning
confidence: 99%
“…Multiwall carbon nanotubes (MWNTs) were solubilized by interaction with sulfonated polyaniline (SPAN), which was prepared by in situ polymerization of aniline onto the nanotubes, followed by sulfonation with chlorosulfonic acid in an inert solvent and hydrolysis in water [128]. In a related work, single wall carbon nanotubes (SWNT) were made soluble by covalent linking of poly(m-aminobenzene sulfonic acid) [129,130]. The solubility of functionalized polyanilines in various solvents, obtained by combinatorial functionalization (see above), could be then extended to the dispersion/solubilization of carbon nanotubes by polymer wrapping.…”
Section: Stabilization Of Carbon Nanotubes Dispersion/solution By Wramentioning
confidence: 99%